Frequency and risk factors of sarcopenia in the elderly people - Yu. A. Safonova; N. V. Toroptsova (Klinicist)
Aim. To determine the frequency and assess the risk factors of sarcopenia (SP) in elderly people living at home.Materials and methods. The study included 230 people aged 65 years and older who lived at home and were observed in outpatient clinic. To detect SP, grip strength was measured and muscle mass was determined using dual-energy absorptiometry (DXA). Severe SP was diagnosed based on the results of Short physical performance battery (SPPB) and the “Up and Go” test. The diagnosis of SP was made according to the criteria of EWGSOP2 (2018). The laboratory examination included clinical and biochemical blood analysis, determination of the level of 25 (OH) D.Results. Probable SP was found in 64.8 %, confirmed SP – in 28.7 %, and severe SP – in 21.3 % of older people. The frequency of SP increased with age from 19.6 % in 65–74 years to 52.9 % in 85 years and older (p <0.05). The results of multivariate analysis showed that the probability of SP increased with a BMI of less than 25 kg / m2 (OR 5,459; 95 % CI: 1,939–15,369; p = 0.0013), severe comorbidity calculated by the Charlson index (OR 5,178; 95 % CI: 1,597–14,128; p = 0.0030) and the presence of such laboratory indicators like level 25 (OH) D less than 20 ng / ml (OR 4,989; 95 % CI: 1,321–12,626; p = 0.0420), total protein less than 64 g / l (OR 8,567; 95 % CI: 2,658–27,617; p = 0.00032), CRP more than 5 mg / l (OR 14,279; 95 % CI: 3,511–58,071; p = 0.00020) and moderately reduced renal function (GFR <60 ml / min / 1.73 m (OR 12,108; 95 % CI: 3,944–37,170; p = 0.00001).Conclusions. Among elderly people, a high frequency (28.7 %) of SP was detected, which increased with age. A BMI of less than 25 kg / m2, a deficiency of 25(OH)D, total protein level of less than 64 g / l and CRP of more than 5 mg / l, a decrease in GFR of less than 60 ml / min were associated with the presence of SP.